PEMENUHAN KEBUTUHAN PENINGKATAN KETERAMPILAN TENAGA KERJA MELALUI MASSIVE OPEN ONLINE COURSES (MOOCS) - Noramti Mardianti Manurung; Fitriani Tupa Ronauli Silalahi (MUST: Journal of Mathematics Education, Science and Technology, 2024)
Higher education in Indonesia is experiencing rapid development in line with the demands of globalization and industrial revolution 4.0. Dynamic changes in the world of work demand new skills and continuous improvement of competencies. Massive Open Online Courses (MOOCs) are an innovative form of educational courses that can be accessed online via the internet. MOOCs offer open access to learning materials and are designed to accommodate participation from a large number of participants without physical limits on the number of participants. Education has a crucial role in creating quality human resources in the context of progress and challenges of globalization. Technical progress requires superior and competitive human resources, so appropriate and effective thinking and action is needed to overcome low learning outcomes in an effort to improve the quality of education. The research applies a quantitative analysis approach by adopting the Partial Least Square (PLS) method. The research presents recommendations for the development of MOOCs in accordance with the Technology Acceptance Model.